2019
DOI: 10.3390/jcm8040506
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antithrombotic Regimen and Platelet Inhibition Extent on Leaflet Thrombosis Detected by Cardiac MDCT after Transcatheter Aortic Valve Replacement

Abstract: The impact of antithrombotic regimen and platelet inhibition extent on subclinical leaflet thrombosis (SLT) detected by cardiac multidetector computed tomography (MDCT) after transcatheter aortic valve replacement (TAVR) is not well established. Hypoattenuation affecting motion (HAM) has been proposed as a surrogate marker of SLT, and is characterized by hypoattenuated leaflet thickening (HALT) and concomitant reduction in leaflet motion (RELM). We sought to investigate (i) the prevalence of HAM and HALT after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…25,26 The recent demonstration that the development of bioprosthetic valve thrombosis is mainly platelet-independent emphasizes a primary role for contact phase and more likely to be efficiently targeted by OACs. 27,28 Initial enthusiasm for a liberal use of OACs was damped by the early discontinuation of the GALILEO study. 29 In this trial, efficacy and tolerance evaluation of rivaroxaban 10 mg/day combined with aspirin 75 mg/day for 3 months compared with conventional DAPT for 3 months showed an increase in all-cause mortality, thromboembolic, and bleeding events in the rivaroxaban group.…”
Section: Optimal Treatment To Prevent Ischemic Strokementioning
confidence: 99%
“…25,26 The recent demonstration that the development of bioprosthetic valve thrombosis is mainly platelet-independent emphasizes a primary role for contact phase and more likely to be efficiently targeted by OACs. 27,28 Initial enthusiasm for a liberal use of OACs was damped by the early discontinuation of the GALILEO study. 29 In this trial, efficacy and tolerance evaluation of rivaroxaban 10 mg/day combined with aspirin 75 mg/day for 3 months compared with conventional DAPT for 3 months showed an increase in all-cause mortality, thromboembolic, and bleeding events in the rivaroxaban group.…”
Section: Optimal Treatment To Prevent Ischemic Strokementioning
confidence: 99%
“…Anticoagulation seems to reduce the occurrence of subclinical LT more effectively than antiplatelets. Despite the RESOLVE and SAVORY registries mentioned in this article, the FRANCE‐TAVI registry experiment, which investigated subclinical thrombotic events in 12 804 patients, showed that LT rates were significantly lower in patients who received an anticoagulation regimen . Jimenez et al observed that lack of oral anticoagulant therapy at discharge was an independent predictor of MDCT‐defined LT in patients following TAVR.…”
Section: Discussionmentioning
confidence: 89%
“…JCM [20] TAVR: n = 85 114 days (median interval) -Mean transaortic gradient at 30 days and 1 year was similar between patients with and without subclinical leaflet thrombosis.…”
Section: Jimenez Et Almentioning
confidence: 89%
“…Thus, it is unlikely that patients received therapeutic anticoagulation at the time of CT in this series. Multiple other studies have reported a protective role of anticoagulation for subclinical leaflet thrombosis [13,18,20,25].…”
Section: Anticoagulation Is Protective For Subclinical Leaflet Thrombosis and Clinical Thv Thrombosismentioning
confidence: 95%